A Review On Lignin And Biodelignification (Journal of Engineering and Health Sciences, 2019)
Lignin is a complex phenylpropanoid polymer which present between the cell-wall of plant cells and the second largest biomass after cellulose. This structural component is important in plant as they provide physical strength imparting stiffness to the plant cells that enables the plant to transport water and solutes through the treachery elements in plant vasculature system. In pulp and paper industry, delignification is an important step to produce high quality of fiber for paper making. Nevertheless, hindrance from lignin recalcitrant has make pulping process inefficient in both chemical and mechanical methods. This has resulted in pulping process to use more chemicals, high energy consumption and releasing pollutants to the environments. A greener technology or enzyme-based processing might be one of the alternative to improve pulping process. Researchers have been studied to remove lignin using enzymes produced by isolated microorganism from the gut of wood feeding insects or soil. This paper will provide a review on lignin and previous studies about lignin degradation using enzymes such as lignin peroxidase, manganese peroxidase, versatile peroxidase, dye-decolorizing peroxidase and laccase. The discussion in this paper is focused on issues pertaining the efficiency of using enzymes to degrade lignin which also known as bio-delignification. Also, the challenges in implementing bio-based method for pulping process is mentioned in this paper.